Attachment goes to court: child protection and custody issues - Forslund, Tommie; Granqvist, Pehr; van IJzendoorn, Marinus H.; Sagi-Schwartz, Avi; Glaser, Danya; Steele, Miriam; Hammarlund, Marten; Schuengel, Carlo; Bakermans-Kranenburg, Marian J.; Steele, Howard; Shaver, Phillip R.; Lux, Ulrike; et al. (My University, 2022)
Attachment theory and research are drawn upon in many applied settings, including family courts, but misunderstandings are widespread and sometimes result in misapplications. The aim of this consensus statement is, therefore, to enhance understanding, counter misinformation, and steer family-court utilisation of attachment theory in a supportive, evidence-based direction, especially with regard to child protection and child custody decision-making. The article is divided into two parts. In the first, we address problems related to the use of attachment theory and research in family courts, and discuss reasons for these problems. To this end, we examine family court applications of attachment theory in the current context of the best-interest-of-the-child standard, discuss misunderstandings regarding attachment theory, and identify factors that have hindered accurate implementation. In the second part, we provide recommendations for the application of attachment theory and research. To this end, we set out three attachment principles: the child's need for familiar, non-abusive caregivers; the value of continuity of good-enough care; and the benefits of networks of attachment relationships. We also discuss the suitability of assessments of attachment quality and caregiving behaviour to inform family court decision-making. We conclude that assessments of caregiver behaviour should take center stage. Although there is dissensus among us regarding the use of assessments of attachment quality to inform child custody and child-protection decisions, such assessments are currently most suitable for targeting and directing supportive interventions. Finally, we provide directions to guide future interdisciplinary research collaboration.
Keywords: attachment theory; best interests of the child; child custody; child protection; family court; consensus statement